2019
DOI: 10.1021/acs.chemmater.8b05187
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Polar Heterogeneities and Branching Bi-Displacement Directions in K0.5Bi0.5TiO3

Abstract: K0.5Bi0.5TiO3 (KBT) -one of the few perovskite-like ferroelectric compounds with room-temperature tetragonal symmetry -differs from other members of this family (BaTiO3 and PbTiO3) by the presence of a disordered mixture of K and Bi on cuboctahedral sites. This disorder is expected to affect local atomic displacements and their response to an applied electric field. We have derived nanoscale atomistic models of KBT by refining atomic coordinates to simultaneously fit neutron/X-ray totalscattering and extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…Macroscopically, this is observed in BaTiO 3 ceramics as large relative permittivities, large polarizations, and large field induced electromechanical strains. This is also clearly relevant to other systems where these contrasting structural length scales influence the material response such as in relaxor ferroelectrics 24 . Thus, materials systems in which there is a disconnect between the long-range average structure and local structural arrangements are of both scientific and technological interest.…”
Section: Discussionmentioning
confidence: 87%
“…Macroscopically, this is observed in BaTiO 3 ceramics as large relative permittivities, large polarizations, and large field induced electromechanical strains. This is also clearly relevant to other systems where these contrasting structural length scales influence the material response such as in relaxor ferroelectrics 24 . Thus, materials systems in which there is a disconnect between the long-range average structure and local structural arrangements are of both scientific and technological interest.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, in solid solutions including Bi ions, such as BF-BT 46,47 and BNT 48 , offcentering of the Bi ions was observed. It was reported that the change in the Bi sites from six to ten split sites involved a phase transition from paraelectric (cubic) to ferroelectric phases (tetragonal) in K 0.5 Bi 0.5 TiO 3 22 . However, the partial ordering under an applied electric field is not discussed in the ferroelectric phase.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, detailed studies of local structures in Bi-based solid solutions were reported. It was suggested that the Bi displacements change as a function of temperature, and that a phase transition could be associated with the ferroelectric response 22 . Moreover, it was reported that the high piezoelectric response appeared by the local distortion in pseudocubic symmetry under an electric field 23 .…”
mentioning
confidence: 99%
“…Relaxor ferroelectrics, with frequency dispersion of their permittivity, 62 are usually described in terms of polar nanoregions caused by modulations on the cation sublattice. 63 Experimental and theoretical work on other layered materials has suggested a new class of relaxor ferroelectrics, “digital relaxors”. 15 , 64 In these systems, it is the disorder on the oxide sublattice due to the relatively shallow energy landscape (giving several structures of similar energies due to the 2D nature of these materials with perovskite blocks relatively decoupled) that gives rise to short-range polar regions.…”
Section: Discussionmentioning
confidence: 99%